Pengelolaan PAUD Inklusi Berbasis Pendidikan Islam - Fadilatul Fitria; Sukma Nur Ha'yati; Briyantika Puji Lestari (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
Inclusive education offers opportunities for all students, including those with special needs and exceptional talent. Its importance is often misunderstood, especially in early childhood settings, and few institutions practice it, limiting services for many children. Therefore, raising awareness and understanding about the benefits of inclusive education is crucial for ensuring equal educational opportunities. This study aims to strengthen the understanding and practice of Islamic-based early childhood education using a descriptive qualitative case study. Data was collected via interviews, observation, and documentation. Analysis involved data reduction, presentation, conclusion drawing, and verification. Results show: (1) Planning covers learning programs, assistant teachers, admissions team, facilities, and finance. (2) Implementation involves learning programs, teacher training, initial assessments, provision of facilities, parenting, and health services. (3) Evaluation assesses programs, teacher supervision, and infrastructure. In addition, the involvement of various stakeholders such as teachers, parents, and the community is essential to create a supportive environment for inclusive education. This study contributes to inclusive education theory and practice, impacting policy and improving the quality of inclusive, humanistic, Islamic-based early childhood education.